1988
DOI: 10.1111/j.1469-8137.1988.tb03708.x
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of pollen from various coniferous and broad–leaved trees to combinations of acidity and trace metals

Abstract: SUMMARYThe effects of acidic and trace element components of polluted rain on pollen germination and tuhe growth iv vitro are described. The sensitivity of pollen to pH in vitro was related to the species' position in canopy and was different for conifers and hroad-Ieaved trees. Most pollen assayed revealed significant inhibition of germination and germ tuhe growth in response to pHs currently observed in rain samples in eastern Canada. Acer saccharum Marsh and Betula alleghaniensis Britt. pollen m vitro showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Whether overcorrection or overcompensation is involved, hormesis might be associated with organism sensitivity to toxic substances; like response to inhibitory doses, response of organisms to stimulatory doses of toxic substances might also be related to their tolerance to stresses, in view of the stimulation being a disruption to homeostasis as well. There has been evidence that pollen exhibiting hormesis usually has higher LD values when exposed to copper (Cox, 1988). In Mimulus guttatus, clones whose sporophytes are tolerant to copper exhibit pollen hormesis, whereas those that are nontolerant do not display pollen hormesis (Searcy and Mulcahy, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether overcorrection or overcompensation is involved, hormesis might be associated with organism sensitivity to toxic substances; like response to inhibitory doses, response of organisms to stimulatory doses of toxic substances might also be related to their tolerance to stresses, in view of the stimulation being a disruption to homeostasis as well. There has been evidence that pollen exhibiting hormesis usually has higher LD values when exposed to copper (Cox, 1988). In Mimulus guttatus, clones whose sporophytes are tolerant to copper exhibit pollen hormesis, whereas those that are nontolerant do not display pollen hormesis (Searcy and Mulcahy, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore 2-h incubations were used in the present study (Table 1). The incubations were terminated by the addition of 50 L 50% acetic acid to the culture solution (Cox, 1988). Slides were examined under a microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was reported that copper is extremely important for the development of normal pollen (Graham 1975), that wheat pollen is nonviable under copper-deficiency conditions (Graham 1986), and that temporary copper deficiencies significantly reduce wheat pollen viability (Graham 1975). Also, Read et al (1993) found that Cu-(II) salts play an important role in pollen-tube development in a Nicotiana species, and Cox (1988) reported a synergistic effect of pH and Cu on pollen function of Populus tremuloides; the latter author reported that lead significantly inhibits both pollen germination and tube growth of Pinus species, whereas zinc has little or no effect.…”
Section: Pollen Viability and Heavy Metal Concentration In Plant Tissuesmentioning
confidence: 96%
“…Several degenerative processes in the pollen cells of plants growing on polluted soils have been reported (Cox, 1988a;Micieta and Murin, 1999;Koscinska-Pajak, 2000). Under controlled conditions, pollen mother cells clearly show genotoxic effects of heavy-metal ions, being even more sensitive than the widely used micronucleus tests with meristematic root tip cells (Steinkellner et al, 1998).…”
Section: Introductionmentioning
confidence: 95%